Intramolecular bonding as a design strategy for robust intermolecular binding of oligomers - Mohammed Suliman Alshammasi; R. Kenton Weigel; Christopher A. Alabi; Fernando A. Escobedo (Proceedings of the National Academy of Sciences, 2026)
In this study, a combined multiscale-modeling and experimental framework is presented to elucidate design rules to optimize the binding thermodynamics and kinetics of sequence-defined oligomers. It is shown that, contrary to conventional notions, entropy can be designed to favor not only binding affinity but also the rapid hybridization of stable complementary complexes. This entropic gain of binding arises from a strategic interplay between intermolecular contacts and intramolecular interactions that maintain restricted oligomer conformations when unbound. Furthermore, our analysis underscores the important role that solvent quality plays in modulating this interplay through structural changes upon binding in both the oligomers and their solvation shells. While these insights are in principle chemistry-agnostic and can be deployed for a wide range of materials platforms and applications, oligocarbamates are used as testbeds for experimental validation. Oligocarbamates are economical DNA-mimics that, unlike DNA-based constructs, form stable Watson–Crick bonds in common nonaqueous solvents, are not susceptible to enzymatic degradation and can be economically produced at scale.